2019
DOI: 10.1097/qad.0000000000002221
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the potential impact of providing preexposure prophylaxis in pregnant and breastfeeding women in South Africa

Abstract: Objective: HIV-uninfected pregnant and breastfeeding women are at high risk of HIV acquisition, contributing to vertical transmission. Pre-exposure prophylaxis (PrEP) is safe in pregnancy, but PrEP in pregnancy is not policy in many countries including South Africa (SA). We evaluated the potential impact of providing PrEP for pregnant/breastfeeding women using a HIV model for SA. Methods: Our model considers two scenarios: a conservative scenario that matches the experience reported in the Kenyan PrEP programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…South Africa has also recently approved PrEP for pregnant women [ 15 ]. The provision of PrEP for high–risk women at ANC clinics could substantially reduce new HIV acquisition during pregnancy and postpartum as well as vertical transmission of HIV [ 51 ]. This study has identified risk factors that should be considered in prioritizing women for PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has also recently approved PrEP for pregnant women [ 15 ]. The provision of PrEP for high–risk women at ANC clinics could substantially reduce new HIV acquisition during pregnancy and postpartum as well as vertical transmission of HIV [ 51 ]. This study has identified risk factors that should be considered in prioritizing women for PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-exposure prophylaxis in pregnant and breastfeeding mothers can reduce vertical transmission by 40%. 13 Pre-exposure prophylaxis is safe in breastfeeding – with minimal infant-drug exposure. 14 The use of PrEP as part of a comprehensive package of interventions in countries with a high HIV prevalence is endorsed by the WHO in both antenatal and postnatal care.…”
Section: Changes In the Hiv Epidemic Over The Past Decade: Estimates mentioning
confidence: 99%
“…Acceptability and feasibility have been reported in qualitative studies from the region [36‐39]. Modelling studies also suggest that integration of PrEP into antenatal services could significantly reduce the number of new HIV infections [40,41]. The identification of pregnant and breastfeeding women at highest risk of HIV acquisition could make this potential yield even greater.…”
Section: Resultsmentioning
confidence: 99%